Destabilization of Raf-1 by geldanamycin leads to disruption of the Raf-1-MEK-mitogen-activated protein kinase signalling pathway. - Schulte, T W (1996)
The serine/threonine kinase Raf-1 functions downstream of Rats in a signal transduction cascade which transmits mitogenic stimuli from the plasma membrane to the nucleus. Raf-1 integrates signals coming from extracellular factors and, in turn, activates its substrate, MEK kinase. MEK activates mitogen-activated protein kinase (MAPK), which phosphorylates other kinases as well as transcription factors. Raf-1 exists in a complex with HSP90 and other proteins. The benzoquinone ansamycin geldanamycin (GA) binds to HSP90 and disrupts the Raf-1-HSP90 multimolecular complex, leading to destabilization of Raf-1. In this study, we examined whether Raf-1 destabilization is sufficient to block the Raf-1-MEK-MAPK signalling pathway and whether GA specifically inactivates the Raf-1 component of this pathway. Using the model system of NIH 3T3 cells stimulated with phorbol 12-myristate 13-acetate (PMA), we show that GA does not affect the ability of protein kinase C alpha to be activated by phorbol esters, but it does block activation of MEK and MAPK. Further, GA does not decrease the activity of constitutively active MEK in transiently transfected cells. Finally, disruption of the Raf-1-MEK-MAPK signalling pathway by GA prevents both the PMA-induced proliferative response and PMA-induced activation of a MAPK-sensitive nuclear transcription factor. Thus, we demonstrate that interaction between HSP90 and Raf-1 is a sine qua non for Raf stability and function as a signal transducer and that the effects observed cannot be attributed to a general impairment of protein kinase function.